2019
DOI: 10.1088/1361-6471/ab1e64
|View full text |Cite
|
Sign up to set email alerts
|

Elliptic flow of hadrons in Au + Au collisions at $\sqrt{{s}_{\mathrm{NN}}}=7.7,19.6$ and 39 GeV from a multi-phase transport model based on a dynamical quark coalescence mechanism

Abstract: We present a study of the transverse momentum (pT) spectra and the differential elliptic flow (v2) in a multi-phase transport model based on a dynamical quark coalescence model for Au + Au collisions at and 39 GeV. We have compared our results with the experimental data. The v2 of is found to be sensitive to the size parameter for mesons in the model. Our study indicates that the elliptic flow splitting between p and at lower energies may be partly due to quark coalescence in phase space.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…Consequently, after introducing the DQCM to the AMPT model, the yield of π + just after hadronization is increased by about 7.9%, 8.6% The extra π + corresponds to the reduction of ρ + . Even so, the transverse momentum spectrum of final state hadrons from the original AMPT and the DQCM AMPT all agree with the experimental data [34].…”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…Consequently, after introducing the DQCM to the AMPT model, the yield of π + just after hadronization is increased by about 7.9%, 8.6% The extra π + corresponds to the reduction of ρ + . Even so, the transverse momentum spectrum of final state hadrons from the original AMPT and the DQCM AMPT all agree with the experimental data [34].…”
Section: Resultssupporting
confidence: 69%
“…Recently, the improved quark coalescence [30] is used in the AMPT model to analyses of twoparticle angular correlations, and found that the new quark coalescence and parton interactions are mainly responsible for the depression feature in baryon pair angular correlations [33]. And our previous work indicates that the elliptic flow splitting between p and p at lower energies may be partly due to quark coalescence in phase space [34].…”
Section: Dqcm Ampt and Analysis Methodsmentioning
confidence: 95%
See 1 more Smart Citation